2014
DOI: 10.1118/1.4883882
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic keyhole: A novel method to improve MR images in the presence of respiratory motion for real-time MRI

Abstract: This study demonstrates that the dynamic keyhole method is a promising technique for clinical applications such as image-guided radiotherapy requiring real-time MR monitoring of the thoracic region. Based on the results from this study, the dynamic keyhole method could increase the temporal resolution by a factor of five compared with full k-space methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The dynamic keyhole method is comprised of library acquisition (full k-space datasets) and central k-space dataset acquisition (central k-space datasets). 32 A keyhole size, the size of the central k-space datasets is determined using the full k-space datasets [i.e., full k-space datasets = peripheral k-space datasets + central k-space datasets (keyhole)] at similar respiratory states prior to the central k-space dataset acquisition. Then, the central k-space datasets are obtained to be combined with the library of peripheral k-space datasets at the corresponding respiratory state in displacement and phase (where phase is simply used to determine whether the breathing is inhale to exhale or exhale to inhale).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic keyhole method is comprised of library acquisition (full k-space datasets) and central k-space dataset acquisition (central k-space datasets). 32 A keyhole size, the size of the central k-space datasets is determined using the full k-space datasets [i.e., full k-space datasets = peripheral k-space datasets + central k-space datasets (keyhole)] at similar respiratory states prior to the central k-space dataset acquisition. Then, the central k-space datasets are obtained to be combined with the library of peripheral k-space datasets at the corresponding respiratory state in displacement and phase (where phase is simply used to determine whether the breathing is inhale to exhale or exhale to inhale).…”
Section: Methodsmentioning
confidence: 99%
“…In the previous study, 32 full k-space datasets were continuously obtained at a set acquisition interval (i.e., 200 ms) over five respiratory cycles so that multiple full k-space datasets could be obtained for each displacement bin. This required extra time to process the multiple full k-space datasets acquired during the library acquisition phase of the dynamic keyhole method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conventional data sharing techniques such as keyhole imaging, high‐temporal resolution is accomplished by reducing the amount of temporal k‐space data acquired in real‐time (called keyhole data) and high‐spatial resolution imaging is achieved by utilizing prior peripheral k‐space data in conventional Fourier transform image reconstruction . By utilizing anatomical motion information such as respiratory displacement in keyhole imaging, real‐time 2D MRI in the presence of respiratory motion (i.e., dynamic keyhole imaging) can be acquired without noticeable motion artifacts . The previous studies demonstrated that the dynamic keyhole 2D cine imaging provided accurate tumor motion quantification with higher frame rates (~15 frames/sec), implying a promising technique for real‐time 3D cine MRI.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] In addition to the need for motion correction for improved MR imaging, the recent incorporation of MRI in hybrid imaging systems (e.g., PET-MRI) has increased interest in using MRI to improve PET image quality (though motion compensation). [15][16][17][18] Furthermore, MRI-guided radiotherapy is also being investigated as it provides an opportunity to monitor and correct for motion, [19][20][21][22][23] which impedes accurate targeting and delivery of therapy. 19,24 In the development and validation stages of motion measurement and correction techniques, it is important to be able to simulate physiological motion within the MRI scanner, for example, for studies developing respiratory motion correction techniques.…”
Section: Introductionmentioning
confidence: 99%